Experimenting with illusions - Gardner, Robert, 1929- (New York : F. Watts, 1990)
Explains how visual perceptions are processed and suggests how illusions can be produced with images and graphics.
Includes bibliographical references.
Booklist starred.
School Library Journal.
Wilson's Junior High School.
7.4
7.4
Keywords: Optical illusions -- Juvenile literature; Visual perception -- Juvenile literature; Optical illusions; Visual perception; Optical illusions; Perception